Practicing History - New Direction In Historical Writing After The Linguistic Turn - Shihade, Magid (Teaching History: A Journal of Methods, 2007)
Practicing History consists of debates on theoretical analysis in the last twenty-five years and on the tools of understanding and analyzing the past. In the preface and introduction Gabriel Spiegel provides context and background to the debates in the field and summarizes the main arguments. Spiegel divides the book into three sections containing thirteen chapters written by well known scholars in the field such as Pierre Bourdieu, Michel de Certeau, Anthony Giddens, and Joan Scott, to name only a few.